2020
DOI: 10.3390/w12113121
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Doped Graphene Iron-Based Particle Electrode Outperforms Activated Carbon in Three-Dimensional Electrochemical Water Treatment Systems

Abstract: The synergy between electrochemical oxidation and adsorption on particle electrodes was investigated in three-dimensional (3D) systems for p-nitrosodimethylaniline (RNO) decolorization and pesticide removal. A comparison was made between granular activated carbon (GAC) and a novel synthesized nitrogen-doped graphene-based particle electrode (NCPE). Experiments on RNO decolorization show that the synergy parameter of the 3D-NCPE system was improved 3000 times compared to the studied 3D-GAC system. This was due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…Although this process reduced the overall volume and sludge, it is quite expensive due to the high operating cost associated with the generation of ozone [21]. Electrochemical oxidation [22] and Fenton peroxidation [23] are the most used advanced oxidation processes, all of them efficiently able to decrease COD, color, and toxicity [24]. However, excess sludge formation later requires its disposal or secondary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although this process reduced the overall volume and sludge, it is quite expensive due to the high operating cost associated with the generation of ozone [21]. Electrochemical oxidation [22] and Fenton peroxidation [23] are the most used advanced oxidation processes, all of them efficiently able to decrease COD, color, and toxicity [24]. However, excess sludge formation later requires its disposal or secondary treatment.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no significant differences between the other systems. The results for the tested activated carbon may be explained by the possibility that polarized activated carbon increases the total active electrode surface when exposed to an electric field [60,61].…”
Section: Discussionmentioning
confidence: 97%
“…The institutions that frequently appeared in scientific publications related to the research area are presented in the network map and table (refer to Figure 3 and Table S3). Based on the node size, it can be observed that the most productive institutions were from the People's Republic of China, with the Chinese Academy of Sciences having the highest publication count (22) followed by Tianjin University (publication count 19). Additionally, the Chinese Academy of Sciences (centrality 0.12), the Egyptian Knowledge Bank (EKB) (centrality 0.09), and Zhejiang University (centrality 0.05) It is interesting to note that Great Britain and France showed significant cooperation in the investigated field, although their productivity was not at the top (production 7 and 7, centrality 0.21 and 0.09, respectively, see Table S1).…”
Section: The Contributions Of Institutionsmentioning
confidence: 99%